Transfer of heat and speed of plasma particles to powder particles in the plasma spray process at atmospheric pressure - Mrdak, Mihailo R. (Vojnotehnički glasnik / Military Technical Courier, 2017)
For successful powder deposition and a good quality of deposited layers, the following factors are of great importance: uniform powder injection into the plasma jet, transfer of  heat and velocity of plasma particles (ions and electrons) to powder particles as well as the temperature and speed of molten powder particles before the collision with the substrate. For each powder type, depending on the distribution of particle granulation (µm) and density (kg/m3), it is necessary to determine the amount of powder supply (g/min) in the plasma for defined gas flows (l/min), types of plasma gases (Ar, He, H2, N2 or their mixtures) and power supply levels (kW). For the transfer of heat and speed of plasma particles to powder particles, there must be an interaction between the ions and electrons from the plasma and the powder particles. For already known plasma jet speed and temperature values at atmospheric pressure, trajectories of individual particles can be calculated using the equations of motion taking into account viscous friction and inertia. The paper describes the relation between the speed of Al2O3 powder injection and the velocity of individual Al2O3 powder particles in the plasma depending on the distance from the anode opening, as well as the relation between powder granulation and the temperature of the surface of powder particles depending on powder injection and the level of plasma gun power supply at atmospheric pressure.
Keywords: velocity; transfer; temperatures; powders; plasmas; particles; heating